Association between perioperative surgical home implementation and transfusion patterns in adolescents with idiopathic scoliosis undergoing spinal fusion. Issue 6 (14th April 2019) - Cronin, Jessica A.; Oetgen, Matthew E.; Gordish‐Dressman, Heather; Martin, Benjamin D.; Khan, Nergis; Pestieau, Sophie R.
Summary: Background: Blood transfusions in patients with adolescent idiopathic scoliosis after fusion have been associated with increased morbidity, mortality, and cost. Objective: The aim of this study was to evaluate the association between implementation of blood–conservation strategies within the perioperative surgical home on transfusion rates for patients with adolescent idiopathic scoliosis undergoing spinal fusion. Methods: Two hundred and thirteen patients (44 preperioperative surgical home, 169 postperioperative surgical home) who underwent posterior spine fusion for adolescent idiopathic scoliosis between 23 June 2014, and 30 July 2017, were enrolled in this case control study. The perioperative surgical home implemented in March 2015 involved evidence–based perioperative interventions to create a standardized clinical pathway including judicious use of crystalloid management, restrictive transfusion strategy, routine use of cell saver, and standardized administration of anti‐fibrinolytics. The primary outcome was odds of perioperative transfusion. Secondary outcomes included volumes of crystalloid, albumin, cell saver, packed red blood cells as well as calculated blood loss. Other variables that were documented included antibrinolytic total dose, mean arterial pressure, temperature, laboratory values, intrathecal morphine dosing, and surgical time. Statistical methods included t test and logistic regression. Results: For the postperioperative surgical home, the odds of perioperative transfusion were 0.30 (95% CI 0.13‐0.70), as compared to preperioperative surgical home. In terms of secondary outcomes, calculated blood loss was significantly lower in the postperioperative surgical home patients (27.0 mL/kg preperioperative surgical home vs 22.8 mL/kg postperioperative surgical home; mean difference = −0.24 [−0.44, −0.04]). Although no difference was noted in the amount of intraoperative cell saver or albumin administered, a reduction was noted in mean intraoperative crystalloid given postperioperative surgical home (41.4 mL/kg ± 20.4 mL/kg preperioperative surgical home vs 28.0 mL/kg ± 13.7 mL/kg postperioperative surgical home; log mean difference = 0.37 [95% CI 0.21‐0.53], P  < 0.001). Postperioperative surgical home patients also had a significantly higher temperature nadir (mean difference = −0.47 [95% CI −0.70 to −0.23]; P  < 0.001), received a significantly higher total anti‐fibrinolytic dose (mean difference = −3939 [95% CI −5364 to −2495]; P  < 0.001), and were exposed to shorter surgical times (mean difference = 0.72 [95% CI 0.36‐1.09]; P  < 0.001). Conclusions: Implementation of blood–conservation strategies as part of a perioperative surgical home for patients with adolescent idiopathic scoliosis undergoing posterior spine fusion resulted in significant decrease in perioperative blood transfusions.